Plastic evolution and phase transition mechanisms in γ-TiAl nano polycrystal by a molecular dynamics simulation - Lulu Li; Hang Li; Shanling Li; Lulu Xu; Xiaoli Fan; Junqin Shi (Journal of Materials Research and Technology)
γ-TiAl based alloys are widely regarded as one important high-temperature structural material, however the deformation behaviors are still not clearly clarified. The microscopic plastic deformation and phase transition of γ-TiAl nano polycrystals under compression are investigated by molecular dynamics simulation. The results show that the initial plasticity is dominated by slip of partial dislocations whose continuous formation and secondary slip on the same slip plane result in the generation and disappearance of intrinsic stacking faults (ISFs). At the strain of about 0.2, a continuous structure transformation of “ISF → ESF → TB” is observed, during which the interaction between different ISFs causes the atomic misalignment corresponding to the change in atomic stacking order near ISF. As the compressive strain exceeds 0.2, the FCC-to-BCC phase transition occurs within polycrystals due to the high Mises stress, the high stress level within grains facilitates the expansion of BCC phase from initial FCC phase, and the newly formed BCC phase maintains the atomic-arrangement orderliness of original phase. The interface between FCC and BCC phases obeys the low-energy Kurdjumov-Sachs orientation relationship. This work is helpful for better understanding the atomic-scale deformation behaviors and provides a theoretical guidance for designing high-performance alloy materials.